Mozambique's Debt and the International Monetary Fund's Influence on Poverty, Education, and Health. (April 2016) - Beste, Jason; Pfeiffer, James
For nearly 30 years, Mozambique has been facing austerity measures regulated by the IMF. These austerity measures, grounded in macroeconomic policies, were supposed to lift Mozambique out of poverty, and improve its healthcare and education systems. By taking an in-depth look at the major etiologies of Mozambique's debt and the conditions which forced the country to accept austerity measures-despite their protests-prior to receiving IMF funding, this paper examines how IMF policies over the past 30 years have affected poverty, health, and the education system. The results of these policies have contributed to Mozambique's enduring classification as one of the poorest countries in the world. Aside from economic outcomes, Mozambique also has abysmal health and education systems, with one of the lowest life expectancies in Sub-Saharan Africa. It is time to re-evaluate how the current IMF macroeconomic policies negatively affect, health, education and the socioeconomic status of those who live in abject poverty. As short term macroeconomic policies of PARPA have been ineffective at reducing poverty, promoting education and improving health, the IMF should consider using longer term macroeconomic policies which invest in—rather than limit—public services such as health and education.